Futebol para a vida: o gol de placa é esse. - Marinho, Josiane Moraes (2019)
This research emerged after joining the Post-Graduate Program in Vocational and Technological Education (PROFEPT), which provided me with analyzes and reflections about the contributions that Physical Education (PE) could have within Vocational and Technological Education (EFA) , as a contribution factor for the Integral Human Formation (FHI) of the students. The objective of the research was to develop practical activities, through soccer, aimed at the FHI of the students involved. The research site was the Federal Institute of Pará / Abaetetuba Campus and the subjects were 20 students from the Integrated Technical High School (EM) courses. Through a qualitative approach, we use as data collection the interview, direct observation, field diaries and the focus group, in order to better understand the object investigated. As a way of analyzing the data, we used the content analysis that provided the categories essential for our analysis, where we identified three: Distorted sense and devaluation of EF; EF as a key discipline in EPT and EF and contribution to FHI. For each category found, we write explanatory text. In the category, the distorted sense and the devaluation of EF, we perceive that this sense is something present and striking even today, where inadequate and deteriorated physical structures, the "ball rolling" taking the front of classes, the prevalence of the sport exclusively, the lack of contextualization with social themes, absence of teaching learning process and educational didactic planning, allow the discipline to be devalued and disassociated from the context that the FHI of EMI students seeks. In the category of EF, as a fundamental discipline in EPT, we realize that students do not associate the EMI with the idea of integrality of knowledge, politecnia, work as an educational principle that aims at FHI. However, in spite of all these factors, a large part understands that the discipline has its importance within the EFA as a discipline that diffuses knowledge that seeks to contribute beyond technical training and teachings of rules and gestures, which becomes fundamental in MS. Finally, in the EF category and the contribution to FHI, we realize that the FHI conception is still very vague and its relationship with EF for students is still a slow process, but it must be created and shared, since the idea to train the student not only for the job market, but for the world of work needs to be explored, developed, created, lived by all the actors that are part of the EFA. It is therefore necessary and emergent that EF and sport be re-signified so that we can make sense of the discipline and meaning to students within the context of EFA contributing to FHI. Thus, the development of this study was the creation of a board game, which contemplates themes such as racism, machismo and homophobia in soccer, giving not only new senses to sports practice, but also, providing new possibilities for teaching learning, thus expanding to other disciplines in the most diverse subjects.